A report of new mammalian tapeworm Moniezia osmanabadensis from Capra hircus at Osmanabad district (M.S.) India - Humbe, Atul; Borde, S N; Jadhav, Swati (Journal of Experimental Sciences, 2012)
The present communication deals with the occurrence of a new mammalian tapeworm Moniezia (B) osmanabadensis n.sp. from Capra hircus (L) in Osmanabad district (M.S.) India. It comes closer to all the known species of the genus Moniezia but differs from all the known species of the genus in having the scolex globular, elongated, mature proglottids Craspedote, testes medium in size, rounded scattered posterior to segment, 170-200 in numbers, cirrus pouch oval, ovary compact, bean shaped, vitelline gland post ovarian.